Religionspsykologi som teori om den individuelle religiøsitet - Nørager, Troels (Religionsvidenskabeligt Tidsskrift, 1988)
The first part of this essay deals with some of the theoretical and methodological problems related to the scientific status of psychology. On this basis, the precarious position of psychology of religion is addressed and the author suggests that the discipline’s future is dependent upon realizing the necessity of returning to the original formulation of the task and purpose of psychology of religion, i.e. the creative investigation of the individual’s religion. The second part is a survey of four major positions in the psychology of religion (William James; experimental and psychoanalytic psychology of religion, and approaches from social psychology) and leads, finally, to a brief discussion of some of the more interesting perspectives: (1) the relation between “classic” and “contemporary” approaches of psychology of religion; (2) the influence of secularization and the complementary relation between the scientific perspective of psychology of religion and the self-understanding of religious traditions, groups and persons; (3) the prospect of a future theoretical convergence in psychology of religion.